251 Prognostic role of acute myocardial infarction diagnostic criteria in non-ST segment elevation myocardial infarction. (8th December 2021) - Sansonetti, Angelo; Armillotta, Matteo; Fabrizio, Michele; Angeli, Francesco; Bergamaschi, Luca; Stefanizzi, Andrea; Magnani, Ilenia; Donati, Francesco; Toniolo, Sebastiano; Paolisso, Pasquale; Foà, Alberto; Rinaldi, Andrea; et al.
Abstract: Aims: Although patients with ST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI) share similar risk factors and similar pathophysiology, their outcomes differ considerably. The Fourth Universal Definition of Myocardial Infarction (UDMI) defined acute myocardial infarction (AMI) by an acute myocardial injury together with clinical evidence of acute myocardial ischaemia. However, the prognostic role of each single diagnostic criteria has never been explored. To evaluate the prognostic role of the different diagnostic criteria of AMI according to the Fourth UDMI in patients with STEMI vs. NSTEMI. Methods and results: We enrolled all consecutive patients with AMI undergoing coronary angiogram at our Centre. We used a combination of criteria, according to the current ESC guidelines, to meet the diagnosis, namely the detection of an increase and/or decrease of high-sensitivity cardiac troponin I, with at least one value above the 99th percentile of the upper reference limit and at least one of the following: symptoms of ischaemia; ECG changes (new ST-T changes or new left bundle branch block); development of pathological Q waves in the ECG; echocardiographic evidence of new loss of viable myocardium, or new regional wall motion abnormality. According to the ECG presentation at admission, patients with AMI were divided into STEMI and NSTEMI subgroups. All-cause mortality and a composite endpoint of all-cause mortality, re-hospitalization for heart failure, and myocardial re-infarction were collected. The predictive value of diagnostic criteria alone and their association was evaluated using Kaplan–Meier survival curves and subsequent Cox-regression analysis to find independent predictors of adverse events. 2345 patients were evaluated (41.6% STEMI and 58.4% NSTEMI). The two groups had similar baseline characteristics. The total number of events was 689 (292 in STEMI group and 397 in NSTEMI group). We found that clinical criteria alone showed a positive predictive value in NSTEMI ( P  < 0.001). Moreover, electrocardiographic and echocardiographic criteria correlated with a worse prognosis in STEMI group ( P  < 0.01). No other significant prognostic correlation was found. Multivariable Cox-regression model demonstrated that clinical criteria were the only independent predictors of better prognosis in patients with NSTEMI (HR = 0.48; 95% CI: 0.31–0.74; P  < 0.001). We did not find any predictor of outcome in patients with STEMI (HR = 0.6; 95% CI: 0.3–1.5, P  = 0.3; HR = 1.1; 95% CI: 0.5–2.6, P  = 0.7; HR = 0.6; 95% CI: 0.3–1.2, P  = 0.2 for clinical and echocardiographic criteria alone and their combination, respectively). Conclusions: Our data suggest that in NSTEMI the prognosis is considerably better if clinical criteria alone are present at admission. We hypothesize that the absence of electrocardiographic and echocardiographic alterations in NSTEMI could indirectly indicate smaller infarct sizes or other causes of acute myocardial injury.